Post-Spinal Anesthesia Hypotension during Cesarean Delivery, A Review - Ghalib J Al-asadi (Journal of Global Pharma Technology, 2016)
Maternal hypotension is a common complication after spinal anesthesia for cesarean delivery. Prevention and treatment of post-spinal hypotension (PSH) in cesarean delivery has been frequently investigated. Fluid loading is superior to no-fluid regimen; however, the incidence of PSH is still high with all fluid loading protocols; thus, the use of fluid loading as a sole method for prophylaxis might be not satisfactory for many anesthetists. Phenylephrine is the preferred vasopressor for prevention and management of PSH in most cases. Ephedrine may be more beneficial in patients with bradycardia, patients with uteroplacental insufficiency and pre-eclamptic patients. Norepinephrine infusion was recently investigated as an alternative for prophylaxis of PSH with minimal cardiac side effects. The high incidence of PSH with most of the pharmacological and non-pharmacological methods suggests the need for multimodal protocols for prevention and management of this problem. PSH in cesarean delivery is a common daily situation facing all anesthetists; thus, future research should focus on simple and rapid protocols that can be easily applied by anesthetists with moderate and low experience with minimal need to complex devices or costly drugs.Keyword: Hypotension, Spinal anesthesia, Cesarean delivery.